Composition and in vitro Antimicrobial and Antioxidant Activities of the Essential Oils of Four Thymus Species in Turkey - Azaz, A.D.; Celen, S. (Asian Journal of Chemistry, 2012)
The genus Thymus (Lamiaceae) is represented in Turkey by 38 species. Aerial parts of Thymus canoviridis Jalas (I and II), T. cilicicus Boiss. & Bal., T. comptus Friv. and T. revolutus Celak. collected from different localities of Turkey were subjected to hydro distillation to yield essential oils and analyzed by GC and GC/MS. Thymol was found as the main component in the oils of T. canoviridis (I) (60.44 %), T. canoviridis (II) (64.79 %), T. cilicicus (34.03 %), T. comptus (55.14 %) and T. revolutus (66.96 %). All test bacteria and Candida albicans were inhibited by all the essential oils. The essential oils showed weak antifungal activity against all microfungi tested. Antioxidant activity was tested using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical-scavenging method.